The Relationship between Learning Motivation and Interest in Learning Local Content Subjects in Class X Students at SMA Negeri 2 Makassar - Mahyiyuddin, Abiyyu Arib; Alwi, M Ahkam (Polteknik Ilmu Pemasyarakatan, 2023)
Muatan lokal is a lesson that aims to provide students with knowledge, skills, and behavior so that students have a good insight into the state of the environment and the needs of the community based on the values and rules that apply in the region, supporting the sustainability of regional development and national development. In fact, SMA Negeri 2 Makassar students lack interest in learning in local content subjects. The purpose of this study was to determine the relationship between learning motivation and interest in learning Muatan Lokal in class X students at SMA Negeri 2 Makassar. The research method used in this research is quantitative research The respondents of this study amounted to 296 class X students of SMA Negeri 2 Makassar. The sampling technique in this study used Accidental Sampling. The measuring instruments used are learning motivation scale and learning interest scale. This study used a correlation test analysis technique which obtained the results that there was a relationship between learning motivation and interest in learning local content subjects in class X students at SMA Negeri 2 Makassar. The results of this study indicate that there is a significant relationship between learning motivation and interest in learning in students. The correlation value between learning motivation and interest in learning is 0.914. The value is positive with a correlation that is categorized as strong. The conclusion of the study is that there is a positive relationship between learning motivation and interest in learning local content subjects in class X students at SMA Negeri 2 Makassar.